P1749DECEASED DONOR KIDNEY TRANSPLANTATION IN AHUS: A PROPHYLAXIS-FREE APPROACH EXPERIENCE. (6th June 2020) - Manonelles, Anna; Favà, Alexandre; Montero, Nuria; Melilli, Edoardo; Bestard, Oriol; Cruzado, Josep
Abstract: Background and Aims: Atypical hemolytic uremic syndrome (aHUS) has been associated with high risk for recurrence after kidney transplantation. In 2017, a consensus report on aHUS was published by KDIGO working group whereby eculizumab prophylaxis approach was recommended in renal transplantation. Here we report a series of 5 cases of successful deceased donor kidney transplantation in aHUS affected recipients following a preemptive approach free of Eculizumab treatment. Method: Five patients with history of end stage kidney disease due to aHUS were eligible for kidney transplantation. All of them had a functional and genetic complement pathway evaluation, showing pathologic mutations to CFI, MCP, CFH and CFB respectively. All of them received a cadaveric donor after a selection of optimal donors with minimal delayed graft function risk and low immunological risk. They accomplished a therapeutic strategy of plasmapheresis prior and in 3 cases 5 days after transplantation. After that, an intensive follow-up was performed with hemolyitic parameters monitoring (blood cell count and extension, LDH, haptoglobin, C3 and C4) regularly. The immediate clinical course was uneventful, without hemodialysis requirements nor biochemical microangiophatic anemia signs. One patient received iMTOR maintenance treatment, three patients received a CNI-based therapy with tacrolimus, mycophenolate and steroids, and one patient was treated with belatacept, mycophenolate and steroids. Results: Patients presented an uneventful immediate transplant follow-up, with early graft function recovery and without surgical nor infectious complications. 4 patients completed long follow-up without complications (6 months to 12 years respectively). The patient with belatacept treatment (CFI mutation and MCP risk polymorphism) presented acute aHUS recurrence at 90 days after transplantation, with hypertension, hemolytic anemia, plaquetopenia and acute kidney injury (serum creatinine raised from 115µmol/L to 190µmol/L), but thanks to an early diagnose received immediate treatment with Eculizumab with complete resolution of the event, and with a current optimal outcome of 9 years follow up with normal GFR without proteinuria. Conclusion: It has recently been described the potential benefits from living kidney donors and low tacrolimus use to minimize recurrence rates in aSHU, thereby averting endothelial injury. However, deceased donor transplantation is a beneficial option to patients affected of aHUS CKD without living donors. According to our experience, preemptive plasma therapy could be effective in the prevention of immediate disease recurrence in patients with high risk mutations with deceased kidney donors. Precocious diagnose of recurrence is mandatory and a rapid establishment of treatment with eculizumab brings optimal outcomes. A preemptive approach is safe when intensive clinical and analytical controls are performed, and represent a better cost-effective strategy. More evidence to define risk groups and tailor individualized treatments represent a future prospect in these patients.